2001
DOI: 10.1007/s002100000347
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological characterisation of the decrease in 5-HT synthesis in the mouse brain evoked by the selective serotonin re-uptake inhibitor citalopram

Abstract: The selective serotonin re-uptake inhibitor (SSRI) citalopram decreases the synthesis of 5-hydroxytryptamine (5-HT) in the mouse brain in vivo. The underlying mechanism was studied by recording the accumulation of 5-hydroxytryptophan (5-HTP) in hypothalamus and hippocampus after inhibition of the aromatic amino acid decarboxylase activity with m-hydroxybenzylhydrazine (NSD 1015). Depletion of 5-HT with reserpine markedly reduced the citalopram-induced decrease of 5-HTP but not that evoked by the 5-HT1A recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 40 publications
(55 reference statements)
1
19
0
Order By: Relevance
“…This suggests that the effects of anpirtoline on cognition are mediated by stimulation of the 5-HT 1B receptor. This is consistent with biochemical studies showing that NAS-181 can fully block the decrease in 5-HT synthesis induced by anpirtoline in the mouse (Stenfors et al, 2001).…”
Section: Discussionsupporting
confidence: 92%
“…This suggests that the effects of anpirtoline on cognition are mediated by stimulation of the 5-HT 1B receptor. This is consistent with biochemical studies showing that NAS-181 can fully block the decrease in 5-HT synthesis induced by anpirtoline in the mouse (Stenfors et al, 2001).…”
Section: Discussionsupporting
confidence: 92%
“…Because the inhibition of 5-HT synthesis by citalopram is reversed by 5-HT 1A and 5-HT 1B/1D receptor antagonists (Barton and Hutson, 1999), it has been suggested that autoreceptor activation plays a major role. However, other studies failed to con- firm this and suggested that some other 5-HT receptor subtype contributes (Moret and Briley, 1997;Stenfors et al, 2001). Interestingly, TRP and the activation of TPH by Ca/calmodulin kinase II and protein kinase A enhanced 5-HT 1A receptor-mediated inhibition of dorsal raphe 5-HT neurons (Liu et al, 2005).…”
Section: Discussionmentioning
confidence: 97%
“…SSRI-induced inhibition of 5-HT synthesis depends on the ability of the drugs to enhance endogenous 5-HT tone on 5-HT receptors, which in turn inhibits 5-HT synthesis (Stenfors et al, 2001). Because the inhibition of 5-HT synthesis by citalopram is reversed by 5-HT 1A and 5-HT 1B/1D receptor antagonists (Barton and Hutson, 1999), it has been suggested that autoreceptor activation plays a major role.…”
Section: Discussionmentioning
confidence: 99%
“…At the dose required to inhibit decarboxylase (100 mg/kg ip) in rats, NSD 1015 activates the synthesis of 5-HT by up to 52% depending upon the brain region [Muck-Seler and Diksic, 1995]. Although alternative and possibly more selective amino-acid decarboxylase inhibitors have been described [e.g., Palfreyman et al, 1984], NSD 1015 is still used routinely to block the decarboxylation of 5-hydroxytryptophan (5-HTP) in order to measure its rate of accumulation in the presence and absence of transmitter reuptake inhibitor antidepressants, e.g., citalopram [Stenfors et al, 2001]. All of these antidepressants decrease 5-HT turnover measured by this method (15-50%), which is generally believed to reflect a 5-HT postsynaptic induced negative feedback regulation of 5-HT synthesis [Corrodi and Fuxe, 1969;Carlsson and Lindqvist, 1978].…”
Section: Dual Actions Of the Established Antidepressantsmentioning
confidence: 99%